Primary sclerosing cholangitis - Marina G Silveira; Keith D Lindor (Canadian Journal of Gastroenterology)
Primary sclerosing cholangitis (PSC) is a chronic cholestatic liver disease characterized by inflammation and fibrosis of the bile ducts, resulting in end-stage liver disease and reduced life expectancy. PSC primarily affects young and middle-aged men, often in association with underlying inflammatory bowel disease. The etiology of PSC includes immune-mediated components and elements of undefined nature. A cholestatic picture of liver biochemistries with elevations in serum alkaline phosphatase, nonspecific autoantibodies such as perinuclear antineutrophilic antibody, antinuclear antibodies and smooth muscle antibodies, and diffuse multifocal biliary strictures, resulting in a ‘beaded’ appearance on radiographic studies, are the hallmarks of the disease. No effective medical therapy is currently available, although clinical studies are in progress. Ursodeoxycholic acid at high doses (28 mg/kg/day to 30 mg/kg/day) is the most promising agent but is unproven so far. Liver transplantation is currently the only life-extending therapy for patients with end-stage disease, although recurrent disease can be observed in the transplanted liver. The multiple complications of PSC include pruritus, fatigue, vitamin deficiencies, metabolic bone disease, peristomal varices, bacterial cholangitis, dominant biliary strictures, gallbladder stones and polyps, and malignancy, particularly cholangiocarcinoma, which is the most lethal complication of PSC.